Pengaruh Sikap yang Baik, Integritas, Loyalitas Dan Kepercayaan terhadap Suksesi Pada Bisnis Keluarga Berbasis Family Owned Enterprise (FOE) Generasi Pertama - Brendi Wijaya; Andreas Wijaya; Renaldy Kurniawan (Universitas Bunda Mulia, 2018)
This study aims to determine the succession planning that will be done on family-based company. Family Owned Enterprise (FOE). Subjects In this study used 3 companies that are large-scale enterprises, companies in the medium scale, and companies on a small scale. The company is used as a research subject because this family oriented bussines will face the first succession planning process to a successor candidate who is not from a family member. The purpose of this study is to know in further examine the factors in succession to prospective successors who are not from family members.Keywords: Succession, Family Oriented Business